DEKONSTRUKSI SOSIAL MELALUI FOTO HOAX - Afusa Nidya Kinasih (Specta: Journal of Photography, Arts, and Media, 2019)
Social Deconstruction Through Hoax Photo. The Governor of DKI Jakarta, Basuki Tjahaya Purnama was sentenced to 2 years in prison due to a blasphemy case that occurred in 2016 ago. As a result of this incident, the FPI mass organization (Front Pembela Islam) held an action "411 AksiDamai" which was led directly by FPI chairman Habib Rizieq Shihab with demands to thoroughly investigate Ahok as a suspect in the blasphemy case. On the other hand, the community is separated into two camps. This incident made AganHarahap, a digital artist make creative manipulations, as if Ahok and Habib Rizieq had made peace. In essence, people are dragged by the media to form a social flow that has the power to force. Social currents that may be created in the crowd of cyberspace are seen as contestation of opinion. Agan tried to shake up the political fact into a reality that is formed using Photoshop software.